الإعلان وتقديم الخدمات عبر مواقع التواصلالإعلان وتقديم الخدمات عبر المواقع والتطبيقات الإلكترونية (مجموعات وسائط التواصل الاجتماعي في فيسبوك وواتساب أنموذجاً 2022م) - Sharaf, salih yousif; عبد الله مختار الفكي, أ. عبد الكريم (Gezira Journal of Educational Sciences and Humanities; مجلد 19 عدد 2 (2022), 2023)
هدفت هذه الدراسة إلى تسليط الضوء على دور مجموعات وسائل التواصل الاجتماعي في حل مشكلة التزود بالوقود، كما هدفت إلى معرفة قدرة وسائل التواصل الاجتماعي على جذب الأفراد والتأثير فيهم، وبيان أثر مواقع التواصل الاجتماعي في الرأي العام حول القضايا الخدمية المرتبطة بمعاش الناس. استخدم الباحثان المنهج الوصفي والاستبانة أداة للدراسة. تركزت مشكلة البحث على دراسة أثر مواقع التواصل الاجتماعي في تسهيل نقل البضائع والسلع وحركة المواطنين عبر حصولهم ابتداءً على وقود السيارات (البنزين والجازولين) في ظل أزمة متكررة شهدتها البلاد في السنوات الأخيرة. من نتائج الدراسة: أن استخدام وسائل التواصل الاجتماعي يؤثر إيجاباً في عملية تقديم الخدمات والإعلان عن السلع الأساسية، كذلك فإن وسائل التواصل الاجتماعي قد عززت وأسهمت في إنجاح عمل اللجان والمنظمات والجمعيات المسؤولة عن توزيع السلع الأساسية في ولاية الجزيرة، وأن معظم المحاولات والمبادرات للإفادة من وسائل التواصل الاجتماعي لتوفير السلع الأساسية تعتمد على الجهود الفردية غير المتخصصة. توصلت الدراسة إلى عدد من التوصيات منها: حث مراكز توزيع وبيع السلع الأساسية ومحطات الوقود على استخدام وسائل التواصل الاجتماعي بالقدر الذي يمكّن من خدمة زبائنهم في ولاية الجزيرة، كما أوصت الدراسة بتشجيع المبادرات الخدمية والأعمال التطوعية للمنظمات واللجان والجمعيات التي تتصدى للعمل في مجال التوزيع العادل للسلع الأساسية في ولاية الجزيرة والسودان. This study attempts to shed light on the role of the groups of social media in solving the problem of supplying fuel .The importance of the topic of the study is represented in its relation to the lives of people and the attempts to find solutions to the problems of the society on the one hand , and calling the attention of the government ,the mass media and the researchers to these problems on the other hand. The importance of this study is also represented in that it investigates into a phenomenon that affects one of the most important aspects which are related to the stability and the security of societies .The study aimed at knowing the potentiality of the social media to attract individuals and to affect them .It also aimed at showing the effect of the websites of the  social media on the public opinion with regard to service issues that are related to the lives of people .The researchers adopted the descriptive method where a questionnaire was used for data collection .The research problem centred round the study of the effect of the social media on facilitating the transmission of goods and commodities and the movement of people through , first of all, providing fuel for their cars (Benzene and gasoline ) during the frequent crisis which the country has witnessed in the recent years . Among the most important results of the study is that employing the social media positively  affects the process of offering services and advertisment for the basic goods ; the social media also reinforced and contributed to the success of the work of the  committees,, organizations and  the societies which are responsible for destributing the basic goods in the Gezira State .The study has also revealed that most of the attempts and the initiatives of making use of the socil media to provide the basic goods depend on the non-specialized individual  efforts. The study has come up with some recommendations the most important of which are  : more researches and studies are to be carried out about making use of the social media in offering services and the promotion for ideas , services and new products . The study also recommends that centres of destribution and sales of the  basic goods and fuel stations  are to be encouraged to use  the social media to the extent that is enough for enabling them to serve their customers in the Gezira State . It is also recommended that social media are to be used in encouraging the service initiatives and the work of the volenteer organizations , committees and societies which are  enthusiastically wiiling to work in the field of  fair destribution of the basic goods in the Gezira State .